L'approche de l'école française dans l'étude des antiquités de Tlemcen Al-Zayaniyya - les frères William et George Marcy comme exemple - dahmeche, souhila (Journal of Social Sciences and Humanities, 2025)
French colonialism harnessed all human and material capabilities to extend its control and influence over Algeria. It also worked to obliterate the national identity in various ways and means. Therefore, the colonial authorities employed the pens of their historians, the brush of their painters, and the trowels of their excavators and archaeologists to reformulate the history of Algeria in a way that serves their agenda of distorting our history throughout the ages, which is Their ultimate goal is among all the books and studies concerned with the history of Algeria, and among these books was what was written by the brothers (Georges et William Marcais), whose names were linked to the history of Algeria and its antiquities, especially in the middle period. To prove this, I followed the historical and analytical approach in this study, and among the most important results obtained is that their studies contained many fallacies about the merit of the Tlemcen people in building and constructing their monuments and creativity in them, which are still before us today.